2001
DOI: 10.1046/j.1365-2249.2001.01450.x
|View full text |Cite
|
Sign up to set email alerts
|

Epitope focus, clonal composition and Th1 phenotype of the human CD4 response to the secretory mycobacterial antigen Ag85

Abstract: SUMMARYLymphoproliferation of healthy donors was tested against mycobacterial antigens (PPD, Ag85, Ag85 peptides). All PPD responders recognized the secretory antigen Ag85 and the peptide specificity for Ag85B was defined. Peptide 91±108 was recognized by 85% of donors. In addition, all CD4 T cell lines generated from 12 donors against PPD or Ag85 responded to 91±108. When this peptide was used to generate T cell lines, the cells responded also to tuberculins from atypical mycobacterial species. Thus the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 35 publications
2
22
0
1
Order By: Relevance
“…Concerning T-cell responses in humans, human T-cell epitope mapping of Ag85A has revealed a largely promiscuous recognition pattern, with a majority of healthy M. tuberculosis-and M. leprae-infected subjects with different HLA haplotypes reacting to a restricted number of peptide regions (23). Similar promiscuous T-cell recognition has also been observed for antigen Ag85B in peripheral blood mononuclear cells or T-cell lines from purified protein derivative-positive donors or BCGvaccinated subjects (29,32,34,39).…”
supporting
confidence: 65%
“…Concerning T-cell responses in humans, human T-cell epitope mapping of Ag85A has revealed a largely promiscuous recognition pattern, with a majority of healthy M. tuberculosis-and M. leprae-infected subjects with different HLA haplotypes reacting to a restricted number of peptide regions (23). Similar promiscuous T-cell recognition has also been observed for antigen Ag85B in peripheral blood mononuclear cells or T-cell lines from purified protein derivative-positive donors or BCGvaccinated subjects (29,32,34,39).…”
supporting
confidence: 65%
“…12 Direct ex vivo identification of Ag85-specific T-cell responses without in vitro re-stimulation, however, had not yet been reported. CD4 þ T-cells obtained by from healthy, PPD-skin test positive donors have been reported to focus preferentially on the region 92-108 in Ag85B, 18 which provides the epitope FLTSELPQW (aa 100-108) recognized by HLA-A*2402-restricted T cells.…”
Section: Discussionmentioning
confidence: 99%
“…This peptide was not recognized prior to infection, nor was it recognized in animal 6074, which was nonreactive to Ag85. It has previously been shown that peptides from Ag85A and Ag85B are recognized in a permissive way by PBMCs from healthy PPD-positive human volunteers, with a majority of subjects reacting to a limited number of the same peptides, irrespective of their HLA haplotype (28,40,48). Interestingly, the peptide region spanning aa 141 to 160 from Ag85A was strongly recognized by 90% of these subjects (28), and we have identified in this same region a CD4 ϩ and a CD8 ϩ H-2 drestricted epitope (shared with the Ag85B component) and a CD4 ϩ H-2 b -restricted epitope in, respectively, BALB/c and C57BL/6 mice (12,14).…”
Section: Discussionmentioning
confidence: 99%